HUBUNGAN KONSENTRASI SPM DAN KONDISI CUACA UDARA AMBIEN DENGAN ANGKA KEJADIAN ISPA PADA BALITA DI KECAMATAN SEMARANG BARAT TAHUN 2015-2017 - Endah Rinsania Indi; Budiyono Budiyono; Suhartono Suhartono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
The increasing number of transportation and industry in West Semarang District has caused the increasing of air pollution production, one of them is Suspended Particulate Matter (SPM). The measurements of SPM concentration in West Semarang District on September 2015, August 2017 and September 2017 had exceeded the quality standards (240,95; 243,82; 230,35 µg/m3). This SPM concentration could be causing of ARI on children under five years. The incidence of ARI on children under five years in West Semarang shows an increasing trendline with prevalence of 13,4% in 2017. This study purposed to analyze the relationship between SPM concentration and ambient air weather condition and the incidence of ARI on children under five years. This research was an observational analytic research using time trend ecological study design. Pearson and Rank-Spearman correlation test are used as the data analysis method. The results showed, the average incidence of ARI on children under five years was 296 cases, SPM concentration was 152,76 µg/m3, air temperature was 28,21ºC, air humidity was 77%, and rainfall was 194,72 mm/month. There were no correlation between the incidence of ARI on children under five years and SPM concentration (p=0,263; r=-0,192), air temperature (p=0,872; r=0,028), air humidity (p=0,560; r=0,101) and rainfall (p=0,612; r=0,087). The conclusion of this study is the factor of SPM concentration and ambient air weather were not correlation with the incidence of ARI on children under five years in West Semarang District during 2015 - 2017.